The impact of descriptive norms on motivation to participate in cancer screening: evidence from online experiments - Von Wagner, Christian; Hirst, Yasemin; Waller, Jo; Ghanouni, Alex; McGregor, Lesley M.; Kerrison, Robert S.; Verstraete, Wouter; Vlaev, Ivo; Sieverding, Monika; Stoffel, Sandro Tiziano (Patient education and counseling, 2019)
Objective - The current study tested in two online experiments whether manipulating normative beliefs about cancer screening uptake increases intention to attend colorectal screening among previously disinclined individuals. - Methods - 2461 men and women from an Internet panel (Experiment 1 N = 1032; Experiment 2, N = 1423) who initially stated that they did not intend to take up screening were asked to guess how many men and women they believe to get screened for colorectal cancer. Across participants, we varied the presence/absence of feedback on the participant’s estimate, as well as the stated proportion of men and women doing the screening test. - Results - Across the two experiments, we found that receiving one of the experimental messages stating that uptake is higher than estimated significantly increased the proportion of disinclined men and women becoming intenders. While, we found a positive relationship between the communicated uptake and screening intentions, we did not find evidence that providing feedback on the estimate has an added benefit. - Conclusion - Screening intention can be effectively manipulated through a high uptake message. - Practice implications - Communication of high screening uptake is an easy and effective way to motivate disinclined individuals to engage in colorectal cancer screening.